Battery diaphragm with ion adsorption function and preparation method thereof
By forming a polyimide porous material clad layer on the surface of ceramic particles and used for battery separators, the problem of degradation of cycling performance of lithium-ion batteries is solved, the safety, magnification and cycling performance of the battery are improved, and the high temperature resistance is improved.
Patent Information
- Application Number
- CN202411342874.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-07
AI Technical Summary
During the charging and discharging process of lithium-ion batteries, the non-lithium metal ions of the positive electrode material are easily dissolved and migrated, resulting in a degradation of the battery's cycling performance.
A cladding layer composed of polyimide porous material is formed on the surface of the ceramic particles, and a cladding ceramic particles are formed, and used for the battery separator to effectively adsorb non-lithium metal ions dissolved from the positive electrode of the battery.
It improves the battery's safety, magnification and circulation performance, weakens the battery self-discharge and internal resistance increase caused by impurities, and at the same time improves the high temperature resistance of the battery separator.
Smart Images

Figure BDA0005060198690000091 
Figure BDA0005060198690000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a battery separator with ion adsorption function and a preparation method thereof. Background Art
[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + The electrolyte is then inserted into the negative electrode after being removed from the positive electrode, and the negative electrode is in a lithium-rich state; the opposite is true during discharge. Lithium-ion batteries have become the mainstream of energy storage batteries due to their excellent performance.
[0003] There is a layer of membrane material between the positive and negative electrodes of lithium-ion batteries, usually called a battery separator, which is an important component of lithium-ion batteries. The battery separator has two basic functions: to separate the positive and negative electrodes to prevent short circuits in the battery; and to be wetted by the electrolyte to form a channel for ion migration. At present, the cycle performance of lithium batteries is reduced due to the easy dissolution and migration of non-lithium metal ions in the positive electrode material and the decomposition of the electrolyte and trace water during the charge and discharge process. Summary of the invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a battery separator with ion adsorption function and a preparation method thereof, by forming a coating layer composed of a polyimide porous material on the surface of ceramic particles. After the obtained coated ceramic particles are used for battery separators, they can effectively adsorb non-lithium metal ions dissolved from the positive electrode of the battery, thereby improving the safety, rate and cycle performance of the battery.
[0005] The present invention provides a battery separator with ion adsorption function, comprising a base film and a coating layer located on at least one side of the base film;
[0006] The coating layer comprises coated ceramic particles, wherein the coated ceramic particles comprise a coating layer consisting of a polyimide porous material and a core consisting of ceramic particles.
[0007] In the present invention, the battery separator includes a base film and a coating layer located on at least one side of the base film, the coating layer includes coated ceramic particles, and the coated ceramic particles are coated with a polyimide porous material. On the one hand, the polyimide porous material can effectively adsorb non-lithium metal ions dissolved from the lithium-ion battery, avoiding the migration of metal impurity ions to the negative electrode during the charge and discharge process, which is beneficial to improving the cycle stability of the battery, and reducing the self-discharge behavior of the battery cell caused by impurity elements, and reducing the increase in internal resistance of the battery cell caused by the adsorption of impurity elements on the surface of the negative electrode material; on the other hand, the polyimide porous material has good temperature resistance, and can show excellent thermal protection effect and high-temperature thermal dimensional stability to the obtained battery separator.
[0008] Preferably, the polyimide porous material is obtained by polycondensing aromatic triamine and / or tetraamine with dianhydride monomers;
[0009] Preferably, the amino group / anhydride molar ratio of the aromatic triamine and / or tetraamine to the dianhydride is 0.95-1.05:1.
[0010] In the present invention, aromatic triamines and / or tetraamines can be copolymerized with dianhydrides to construct a polyimide covalent organic framework porous material, which has the advantages of light weight, permanent nanopores, high specific surface area and controllable structure. When coated on the surface of inorganic ceramic particles to form a coating layer, the high specific surface area porous characteristics can enable the ceramic particles to effectively adsorb non-lithium metal ions precipitated during the battery cycle, avoiding the formation of metal precipitates on the negative electrode surface by non-lithium metal ions, while also improving the safety, rate, low temperature and cycle performance of the battery; at the same time, since the surface of the inorganic ceramic particles is coated with the organic material of polyimide, the affinity of the ceramic particles to the organic base membrane can also be improved, thereby achieving the effect of further improving the high temperature protection performance of the battery separator.
[0011] Preferably, the aromatic triamine and / or tetraamine is at least one of 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(4-aminophenoxy)benzene, tris(4-aminophenyl)amine, 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine, 1,3,5,7-tetraaminoadamantane or tetrakis(4-aminophenyl)methane;
[0012] The dianhydride is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride or 4,4'-oxydiphthalic anhydride.
[0013] Preferably, the monomer further comprises a sulfonic acid group-containing diamine;
[0014] Preferably, the sulfonic acid group-containing diamine is at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, 4,4'-diaminodiphenyl ether-2,2'-disulfonic acid, 4,4'-diaminobenzophenone-2,2'-disulfonic acid or 4,4'-diamino-2,2'-biphenyldisulfonic acid.
[0015] In the present invention, by also including a sulfonic acid diamine in the monomer, a sulfonic acid group is introduced into the molecular chain of the polyimide porous material, which can coordinate with lithium ions. On the premise of promoting lithium ion transmission, it also effectively prevents non-lithium metal ions in the electrolyte from being transmitted to the negative electrode, greatly alleviating the phenomenon of lithium precipitation at the negative electrode of the battery, which is beneficial to increasing the ion exchange capacity of the diaphragm, and further improving the charge and discharge efficiency of the battery.
[0016] Preferably, the ceramic particles are at least one of aluminum oxide, boehmite, magnesium oxide, titanium oxide, silicon oxide, zinc oxide or calcium oxide;
[0017] Preferably, the mass of the coating layer is 10-60wt% of the mass of the coated ceramic particles.
[0018] Preferably, the coated ceramic particles are obtained by in-situ reaction of aromatic triamine and / or tetraamine, dianhydride and ceramic particles;
[0019] Preferably, the in-situ reaction temperature is 160-240° C. and the reaction time is 12-24 hours.
[0020] In the present invention, aromatic triamine and / or tetraamine, dianhydride and ceramic particles are mixed and copolymerized to form a coating layer composed of a polyimide type organic framework porous material on the surface of the ceramic particles in situ, thereby giving the ceramic particles an ion adsorption function.
[0021] Preferably, before reacting the aromatic triamine and / or tetraamine, dianhydride and ceramic particles in situ, the ceramic particles are further subjected to coupling reaction with a silane coupling agent containing succinic anhydride;
[0022] Preferably, the silane coupling agent containing succinic anhydride is (3-triethoxysilyl)propyl succinic anhydride.
[0023] In the present invention, succinic anhydride groups can be grafted onto the surface of ceramic particles by coupling reaction between ceramic particles and a silane coupling agent containing succinic anhydride. The succinic anhydride groups can react with aromatic triamines and / or tetraamines added subsequently, thereby penetrating into the in-situ polymerization reaction of aromatic triamines and / or tetraamines and dianhydrides on the surface of ceramic particles. The pore size of the obtained coated ceramic particles is more uniform, and a polyimide porous material with higher crystallinity and better adsorption effect of non-lithium metal ions can be obtained on the surface of the ceramic particles.
[0024] Preferably, the base membrane is at least one of a polyolefin membrane, a cellulose membrane, a polyester membrane, an aramid membrane or a polyimide membrane.
[0025] The present invention also provides a method for preparing the above-mentioned battery separator, comprising: coating a coating slurry including coated ceramic particles on at least one surface of a base film, and drying and curing the coating slurry to obtain the battery separator.
[0026] Preferably, the coating layer slurry further comprises a binder;
[0027] Preferably, the binder is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polymethacrylic acid, polyacrylate, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, butadiene-acrylonitrile polymer or polyvinyl pyrrolidone.
[0028] The present invention provides a battery separator with ion adsorption function and a preparation method thereof, wherein a polyimide porous material coating layer is formed on the surface of inorganic ceramic particles, and the coating layer can adsorb non-lithium metal ions precipitated from the positive electrode, thereby preventing the metal ions from forming transition metal precipitates on the surface of the negative electrode, thereby improving the safety, rate, cycle and other performances of the battery, and also improving the temperature resistance of the battery separator. DETAILED DESCRIPTION
[0029] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0030] Example 1
[0031] A battery separator with ion adsorption function, comprising a polyethylene single-layer separator and a coating layer located on one side of the polyethylene single-layer separator, is prepared by the following method:
[0032] (1) adding pyromellitic anhydride and 1,3,5-tri(4-aminophenyl)benzene in a molar ratio of 1:0.7 to N-methylpyrrolidone and dispersing them uniformly, then adding alumina powder (average particle size of 0.2 μm) with a mass of 4 times that of pyromellitic anhydride and isoquinoline with a mass of 2 times that of pyromellitic anhydride, and dispersing them uniformly by ultrasonication, heating to 200° C. under nitrogen protection, reacting for 18 hours, cooling, filtering, washing, and drying to obtain coated ceramic particles;
[0033] (2) The coated ceramic particles and sodium carboxymethyl cellulose are added to a mixed solvent of water and ethanol (volume ratio of 95:5) at a mass ratio of 100:1, and dispersed evenly by high-speed stirring to obtain a coating layer slurry (solid content of 25wt%); the coating layer slurry is coated on one side surface of a polyethylene single-layer diaphragm (thickness of 12μm, porosity of 45%) by gravure coating to form a coating layer with a thickness of 4μm. After drying at 60°C, the battery diaphragm is obtained.
[0034] Example 2
[0035] A battery diaphragm with ion adsorption function, comprising a polyethylene single-layer diaphragm and a coating layer located on one side of the polyethylene single-layer diaphragm, which is prepared by referring to the method described in Example 1, except that in step (1), pyromellitic anhydride and 1,3,5-tris(4-aminophenoxy)benzene are added to N-methylpyrrolidone in a molar ratio of 1:0.7 and dispersed evenly, and then aluminum oxide powder (average particle size of 0.2 μm) with a mass of 3 times that of pyromellitic anhydride and isoquinoline with a mass of 3 times that of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 160°C under nitrogen protection, reacted for 24 hours, cooled, filtered, washed and dried to obtain coated ceramic particles.
[0036] Example 3
[0037] A battery diaphragm with ion adsorption function, comprising a polyethylene single-layer diaphragm and a coating layer located on one side of the polyethylene single-layer diaphragm, which is prepared by referring to the method described in Example 1, except that in step (1), pyromellitic anhydride and tri(4-aminophenyl)amine are added to N-methylpyrrolidone in a molar ratio of 1:0.7 and dispersed evenly, and then aluminum oxide powder (average particle size of 0.2 μm) with a mass of 5 times that of pyromellitic anhydride and isoquinoline with a mass of 1 times that of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 240°C under nitrogen protection and reacted for 12 hours, cooled, filtered, washed and dried to obtain coated ceramic particles.
[0038] Example 4
[0039] A battery diaphragm with ion adsorption function, comprising a polyethylene single-layer diaphragm and a coating layer located on one side of the polyethylene single-layer diaphragm, which is prepared by referring to the method described in Example 1, except that in step (1), pyromellitic anhydride and 1,3,5,7-tetraaminoadamantane are added to N-methylpyrrolidone in a molar ratio of 1:0.5 and dispersed evenly, and then titanium oxide powder (average particle size of 0.2 μm) with a mass of 4 times that of pyromellitic anhydride and isoquinoline with a mass of 4 times that of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 200°C under nitrogen protection and reacted for 16 hours, cooled, filtered, washed and dried to obtain coated ceramic particles.
[0040] Example 5
[0041] A battery diaphragm with ion adsorption function, comprising a polyethylene single-layer diaphragm and a coating layer located on one side of the polyethylene single-layer diaphragm, which is prepared by referring to the method described in Example 1, except that in step (1), 3,3',4,4'-biphenyltetracarboxylic anhydride and 1,3,5-tri(4-aminophenyl)benzene are added to N-methylpyrrolidone in a molar ratio of 1:0.7 and dispersed evenly, and then aluminum oxide powder (average particle size of 0.2 μm) with a mass of 4 times that of pyromellitic anhydride and isoquinoline with a mass of 4 times that of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 200°C under nitrogen protection, reacted for 16 hours, cooled, filtered, washed and dried to obtain coated ceramic particles.
[0042] Example 6
[0043] A battery separator with ion adsorption function, comprising a polyethylene single-layer separator and a coating layer located on one side of the polyethylene single-layer separator, which is prepared by referring to the method described in Example 1, except that in step (1), pyromellitic anhydride, 1,3,5-tri(4-aminophenyl)benzene and 2,5-diaminobenzenesulfonic acid are added to N-methylpyrrolidone in a molar ratio of 1:0.6:0.2 and dispersed evenly, and then aluminum oxide powder (average particle size of 0.2 μm) with a mass of 4 times that of pyromellitic anhydride and isoquinoline with a mass of 2 times that of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 200°C under nitrogen protection and reacted for 16 hours, cooled, filtered, washed and dried to obtain coated ceramic particles.
[0044] Example 7
[0045] A battery separator with ion adsorption function, comprising a polyethylene single-layer separator and a coating layer located on one side of the polyethylene single-layer separator, which is prepared by referring to the method described in Example 1, except that in step (1), pyromellitic anhydride and 1,3,5-tris(4-aminophenyl)benzene are added to N-methylpyrrolidone in a molar ratio of 1:0.7 and dispersed evenly, and then succinic anhydride alumina powder 4 times the mass of pyromellitic anhydride and isoquinoline 2 times the mass of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 200°C under nitrogen protection, reacted for 16 hours, cooled, filtered, washed and dried to obtain coated ceramic particles;
[0046] The succinic anhydride alumina powder is prepared by adding alumina powder (average particle size of 0.2 μm) to anhydrous ethanol for uniform ultrasonic dispersion, then adding 80 wt% (3-triethoxysilyl)propyl succinic anhydride by weight of the alumina powder, stirring for 12 hours, filtering, washing and drying to obtain the succinic anhydride alumina powder.
[0047] Comparative Example 1
[0048] A battery separator with ion adsorption function, comprising a polyethylene single-layer separator and a coating layer located on one side of the polyethylene single-layer separator, which is prepared by referring to the method described in Example 1, except that step (1) is omitted. In step (2), aluminum oxide powder (average particle size of 0.2 μm) and sodium carboxymethyl cellulose are added to a mixed solvent of water and ethanol (volume ratio of 95:5) at a mass ratio of 100:1, and dispersed evenly by high-speed stirring to obtain a coating layer slurry (solid content of 25 wt%); the coating layer slurry is coated on one side of the polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating layer with a thickness of 4 μm. After drying at 60°C, the battery separator is obtained.
[0049] Comparative Example 2
[0050] A battery diaphragm with ion adsorption function, comprising a polyethylene single-layer diaphragm and a coating layer located on one side of the polyethylene single-layer diaphragm, which is prepared by referring to the method described in Example 1, except that in step (1), pyromellitic anhydride and p-phenylenediamine are added to N-methylpyrrolidone in a molar ratio of 1:1 and dispersed evenly, and then aluminum oxide powder (average particle size of 0.2 μm) with a mass of 4 times that of pyromellitic anhydride and isoquinoline with a mass of 2 times that of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 200°C under nitrogen protection and reacted for 16 hours, cooled, filtered, washed and dried to obtain coated ceramic particles.
[0051] Comparative Example 3
[0052] A battery separator with ion adsorption function, comprising a polyethylene single-layer separator and a coating layer located on one side of the polyethylene single-layer separator, is prepared by referring to the method described in Example 1, except that in step (1), pyromellitic anhydride and 4,4"-diaminoterphenyl are added to N-methylpyrrolidone in a molar ratio of 1:1 and dispersed evenly, and then aluminum oxide powder (average particle size of 0.2 μm) with a mass of 4 times that of pyromellitic anhydride and isoquinoline with a mass of 2 times that of pyromellitic anhydride are added, and after ultrasonic dispersion, the mixture is heated to 200°C under nitrogen protection, reacted for 16 hours, cooled, filtered, washed and dried to obtain coated ceramic particles.
[0053] Performance Testing:
[0054] The battery separators obtained in the above examples and comparative examples were subjected to the following performance tests, respectively, and the results are shown in Table 1 below.
[0055] Thermal shrinkage: The obtained battery separator was cut into a size of 5 cm × 5 cm. The longitudinal (MD) and transverse (TD) dimensions were measured before baking, and recorded as L1 and H1, respectively. The battery separator was then baked at 130 ° C for 1 h, and the MD and TD dimensions were measured again, recorded as L2 and H2, respectively. The MD thermal shrinkage rate was (L1-L2) / L1×100%, and the TD thermal shrinkage rate was (H1-H2) / H1×100%;
[0056] Cycle performance: The obtained battery separator and the positive electrode sheet (lithium cobalt oxide, conductive agent acetylene black, and polyvinylidene fluoride are mixed in an N-methylpyrrolidone solvent in a mass ratio of 97:1:2 to form a positive electrode slurry, which is coated on an aluminum foil and dried, and then cold pressed and stripped to form a positive electrode sheet), the negative electrode sheet (graphite, conductive carbon black SuperP, and styrene-butadiene rubber are mixed in a mass ratio of 97:1:2 in deionized water to form a negative electrode slurry, which is coated on a copper foil and dried, and then cold pressed and stripped to form a negative electrode sheet) and 1 mol / L lithium hexafluorophosphate electrolyte (concentration is 1 mol / L, and the molar ratio of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC is 1:1:1) are assembled into a lithium-ion battery in a conventional manner, and then the battery performance test is performed. Specifically, the charge and discharge cycle is performed at a rate of 1C and 60°C for 500 times, and the capacity retention rate of 500 times is recorded.
[0057] Table 1 Performance test results of the battery separators described in Examples and Comparative Examples
[0058]
[0059]
[0060] As shown in the results in Table 1, compared with the comparative example, the battery separator in the embodiment has better high temperature resistance and high temperature capacity retention rate, and improves the safety, rate, cycle and other performances of the battery.
[0061] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A battery separator with ion adsorption function, characterized in that: It includes a base film and a coating layer located on at least one side of the base film; The coating layer comprises coated ceramic particles, wherein the coated ceramic particles comprise a coating layer consisting of a polyimide porous material and a core consisting of ceramic particles.
2. The battery separator with ion adsorption function according to claim 1, characterized in that: The polyimide porous material is obtained by polycondensing aromatic triamine and / or tetraamine with dianhydride monomers; Preferably, the amino group / anhydride molar ratio of the aromatic triamine and / or tetraamine to the dianhydride is 0.95-1.05:
1.
3. The battery separator with ion adsorption function according to claim 2, characterized in that: The aromatic triamine and / or tetraamine is at least one of 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(4-aminophenoxy)benzene, tris(4-aminophenyl)amine, 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine, 1,3,5,7-tetraaminoadamantane or tetrakis(4-aminophenyl)methane; The dianhydride is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride or 4,4'-oxydiphthalic anhydride.
4. The battery separator with ion adsorption function according to claim 2 or 3, characterized in that: The monomers also include sulfonic acid group-containing diamine; Preferably, the sulfonic acid group-containing diamine is at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, 4,4'-diaminodiphenyl ether-2,2'-disulfonic acid, 4,4'-diaminobenzophenone-2,2'-disulfonic acid or 4,4'-diamino-2,2'-biphenyldisulfonic acid.
5. The battery separator with ion adsorption function according to any one of claims 1 to 4, characterized in that: The ceramic particles are at least one of aluminum oxide, boehmite, magnesium oxide, titanium oxide, silicon oxide, zinc oxide or calcium oxide; Preferably, the mass of the coating layer is 10-60wt% of the mass of the coated ceramic particles.
6. The battery separator with ion adsorption function according to any one of claims 1 to 5, characterized in that: The coated ceramic particles are obtained by in-situ reaction of aromatic triamine and / or tetraamine, dianhydride and ceramic particles; Preferably, the in-situ reaction temperature is 160-240° C. and the reaction time is 12-24 hours.
7. The battery separator with ion adsorption function according to claim 6, characterized in that: Before the aromatic triamine and / or tetraamine, dianhydride and ceramic particles are reacted in situ, the ceramic particles are also subjected to coupling reaction with a silane coupling agent containing succinic anhydride; Preferably, the silane coupling agent containing succinic anhydride is (3-triethoxysilyl)propyl succinic anhydride.
8. The battery separator with ion adsorption function according to any one of claims 1 to 7, characterized in that: The base film is at least one of a polyolefin membrane, a cellulose membrane, a polyester membrane, an aramid membrane or a polyimide membrane.
9. A method for preparing a battery separator according to any one of claims 1 to 8, characterized in that: include: The battery separator is obtained by coating a coating layer slurry including coated ceramic particles on at least one surface of the base film and drying and curing the coating layer slurry.
10. The method for preparing a battery separator according to claim 9, characterized in that: The coating layer slurry also includes a binder; Preferably, the binder is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polymethacrylic acid, polyacrylate, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, butadiene-acrylonitrile polymer or polyvinyl pyrrolidone.
Citation Information
Cited By
Electron-withdrawing group-terminated polyimide covalent organic framework material as well as preparation method and application thereof
CN121293496A
An electron-withdrawing group terminated polyimide covalent organic framework material and a preparation method and application thereof
CN121293496B